THE ROLE OF SPECKLE-TRACKING ECHOCARDIOGRAPHY TECHNIQUE AT THE STAGE OF SUBCLINICAL HEART TRANSPLANT REJECTION - T. V. Stavenchuk; E. D. Kosmachova; A. A. Slavinsky; L. M. Chuprinenko; I. A. Shelestova; K. O. Barbuhatty; V. A. Porkhanov (Вестник трансплантологии и искусственных органов, 2016)
Aim. To identify new predictors of heart transplant rejection by using speckle-tracking echocardiography technique. Materials and methods. 117 recipients were included into research. The follow-up period in S.V. Ochapovsky Region Clinical Hospital No 1 was from March 2010 to April 2015. The groups were allocated based on results of the retrospective analysis of biopsies: group 1 (n = 68), recipients without signs of cellular and humoral rejection (AMR0 ACR0); group 2 (n = 28), recipients with ACR1; group 3 (n = 16), patients with ACR2; group 4 (n = 5), patients with chronic rejection. The analysis of the results was carried out with endomyocardial biopsy, coronary angiography, transthoracic echocardiography (TTE), tissue Doppler imaging, speckle-tracking echocardiography. Results. Early complications include infections and rejection of heart transplant. Cellular rejection is diagnosed in 70% of cases, humoral rejection in 30% of cases. The disease of coronary arteries is a kind of late complications. It was diagnosed in 13.7%. Fraction rejection sensitivity was 63%, specificity was 97% in recipients with ACR1 while carrying out TTE for the purpose of identification of early diagnostic criterion of rejection; recipients with ACR2 had 75% and 96%, respectively. While carrying out PW sensitivity and specificity Е/А in recipients with ACR1 were 83% and 53%, respectively; recipients with ACR2 had 85% and 52%, respectively. While carrying out PW-TDI sensitivity and specificity Е in recipients with ACR1 were 83% and 58%, respectively; recipients with ACR2 had 88% and 60%, respectively. The assessment of myocardial deformation of the left ventricle is as follows: global peak systolic strain in recipients without rejection (GLPS LV) – (–17.54 ± 3.71%), р = 0.0012; recipients with (ACR1, AMR1) had GLPS LV (–10.52 ± 1.8%), p = 0.0012; recipients with ACR2 had (–6.44 ± 1.8%), p = 0.002; recipients with chronic rejection had (–9.43 ± 1.8%), p = 0.002. The STE GLPS LV parameter (–10.52 ± 1.8%), p = 0.0012, which estimates longitudinal function of myocardium can be considered as early diagnostic criterion of myocardium rejection. The correlation coefficient between CD 3, CD 20, CD 68 and parameter GLPS LV% for groups ACR1-ACR2 was 0.54, 0.86 and 0.26, respectively. Conclusions. The parameters of deformation and cardiac mechanics being estimated by means of speckle-tracking echocardiography can be used as diagnostic monitoring of recipients with rejection of heart transplant.